Effect of Lycopene on Caspase-3 Enzyme Activation in Liver of Methanol-Intoxicated Rats: Comparison with Fomepizole - Kurcer, Mehmet Ali; Kurcer, Zehra; Koksal, Mete; Baba, Fusun; Ocak, Ali Riza; Aksoy, Nurten; Sahna, Engin (Mary Ann Liebert, Inc, 2010)
Lycopene is one of the major carotenoids and is found almost exclusively in tomatoes and tomato products. This study was performed to evaluate the effect of lycopene on methanol-induced liver injury and to compare the results with those after fomepizole, which is used in treatment of methanol intoxication. Experiments were carried out with 30 female Wistar rats weighting 180-200 g. Rats were injected with a intraperitoneally dose of 3 g/kg methanol as a 50% solution in isotonic saline once for intoxication. Rats were pretreated with fomepizole (50 mg/kg) and/or lycopene (10 mg/kg) before methanol. After 24 hours all the drug-treated and intoxicated rats were sacrificed under anesthesia. Malondialdehyde (MDA) levels were determined in order to assess lipid peroxidation, and caspase-3 activity was determined by immunostaining of liver tissues to evaluate apoptosis. Methanol administration significantly increased the MDA level and caspase-3 activity in liver. Pretreatment with lycopene and/or fomepizole decreased the MDA levels significantly. Similarly, lycopene and fomepizole decreased methanol-induced caspase-3 activity. The findings of the present study demonstrate that methanol intoxication causes hepatic toxicity in rats and that this is likely a result of reactive oxygen species and apoptosis induction. Lycopene has protective effects against methanol-induced hepatic injury similar to fomepizole. It was demonstrated for the first time that both lycopene and fomepizole prevent methanol-induced hepatic injury by reducing the increase of lipid oxidation and caspase-3 activation.
Keywords: caspase-3; fomepizole; intoxication; liver; lycopene; methanol; rat